انتهاكات حقوق الطفل العراقي في ظل الاحتلال الأمريكي وسبل محاكمة منتهكيها (مجلة الواحات للبحوث والدراسات, 2020)
The Practices Of The United States Forces During The American Invasion Of Iraq Embodied Numerous Gross Violations Of The Rights Of Iraqi Children, Thus Contradicting All The Standards And Foundations Laid Down By International Conventions And Conventions On Human Rights, Including Those That Protect Children's Rights And Provide Special Protection And Care For Them, In The Best Interests Of Children, Which Not Only Violated The Child's Right To Life, But Also Violated The Human Dignity Of The Child, So We Sought Through This Article To Seek Practical Mechanisms To Ensure Justice For The Iraqi People And Steps To Ensure The Stabilization Of The Iraqi People. The Rights Of Iraq And Its Children Against Crimes Committed During The Years Of Siege And Occupation, Including The Punishment Of All Those Who Planned And Participated In The Execution Of Those Crimes And The Payment Of Full Compensation For All Losses. Keywords-Children, U.S. Occupation, Violations, Criminal Responsibility, Compensationمقدمة: